Some bugs glow in the dark - Llewellyn, Claire; Taylor, Myke; Shone, Rob; Moore, Jo (Brookfield, Conn. : Copper Beech Books, 1997)
Provides information about various insects and their physical characteristics, homes, feeding habits, and defenses.
Includes index.
School Library Journal.
L.A. Recommended Foreign Language.
4.2
K-3
Keywords: Insects -- Miscellanea -- Juvenile literature; Insects; Insects; Insects